2021
DOI: 10.1155/2021/9970223
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Environmental Variations in Kernel Color Indices in the Main Almond (Prunus dulcis (Mill.) D.A. Webb) Cultivars Grown in North-Eastern Morocco

Abstract: Color indices are important quality traits that define the consumer visual acceptance and agroindustrial preferences. Little is known regarding these properties in the commercial almond cultivars grown in Morocco. This work aimed at investigating kernel color indices in five cultivars, namely, “Fournat de Brézenaud,” “Tuono,” “Ferragnès,” “Ferraduel,” and “Marcona.” Color indices consisted in the following: brightness (L∗), redness index (a∗), yellowness index (b∗), chroma (C∗), hue (H∗), and metric saturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…among others (Boussakouran et al, 2019;El Yamani et al, 2019a, 2019c, 2020a, 2020b, 2020c, 2020dZeroual et al, 2021;Boussakouran et al, 2021;Sakar et al, 2021aSakar et al, , 2021bIbourki et al, 2022).…”
Section: Principal Component Analysismentioning
confidence: 98%
“…among others (Boussakouran et al, 2019;El Yamani et al, 2019a, 2019c, 2020a, 2020b, 2020c, 2020dZeroual et al, 2021;Boussakouran et al, 2021;Sakar et al, 2021aSakar et al, , 2021bIbourki et al, 2022).…”
Section: Principal Component Analysismentioning
confidence: 98%
“…In contrast, we took over that in our samples stored under nitrogen, no significant color variations were observed in both applied temperatures. More recently, in a study conducted across five sites located in the main almond production regions of Morocco, Sakar et al [44] found that all factors, such as cultivar, growing season, and site, impacted significantly kernel color indices. Nevertheless, the cultivar effect was the principal variability source.…”
Section: Chemical-physical Analysesmentioning
confidence: 99%
“…These by-products, which include hulls, shells, and skins ( Figure 1 ), constitute a significant proportion of the total production volume. In terms of percentage, the hulls account for 52% of the total fresh weight of the almond fruit, the shells represent 33%, the kernel with the skin makes up 15% [ 3 ], and the skin alone represents about 4% [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%